NANOSATELLITE MYSat TO BE LAUNCHED INTO ORBIT - MPRC, Pusat Media & Perhubungan Awam (USM, 2017)
USM, PENANG, 13 January 2017 – A cubeshaped NanoSatellite named MYSat or Malaysia Youth Satellite would be launched into outer space to study the possibility of early detection of earthquakes, the outcome of a research by a group of students and their lecturers from the Universiti Sains Malaysia (USM) School of Aerospace Engineering (PPKA).